Aspectos clínicos, epidemiológicos e mortalidade de pacientes em uso de terapia antifúngica em um hospital universitário - Antonieti, Flávia Maria Pinto Monteiro (2022)
Introduction: Invasive fungal infections are a public health problem with high morbidity and mortality for hospitalized patients, including those on appropriate therapy. Objective: The objective of this study was to evaluate the clinical, epidemiological aspects, and mortality of patients using antifungal therapy admitted to a public hospital. Material and methods: It is a retrospective study carried out in the ward specialized in infectious diseases of a public university hospital in Brazil. Data were collected from medical records of hospitalized patients in the years 2019 and 2020. Results: During the study period, 111 patients used antifungals and death was related to the mean length of hospital stay of 29.35 days (p=0.0252), the mean time of use of antibacterials of 23.5 days (p=0.0164), presence of AIDS (p=0.0397), use of mechanical ventilation (p<0.001) and use of nasoenteral tube (p<0.01). Fungal infection was confirmed in 79 (71.2%) patients who used antifungal. The most frequent fungal agents were Candida spp. (36; 32.4%) and Cryptococcus spp. (22; 19.8%), showing a relationship with mortality (p<0.05 and OR: 7.61 and 5.53, respectively). Regarding the use of antifungal, 56 (50.4%) used it as empirical therapy, 33 (29.7%) as target therapy and 22 (19.8%) as preemptive therapy. Conclusion: Mortality was more frequent among patients with longer hospitalization, who had AIDS, and who used anti-bacterial, mechanical ventilation and nasoenteral tube at some point during hospitalization. The type of antifungal therapy did not influence the mortality of these patients.